Cyclic behaviour analysis of RC elements with plain reinforcing bars - Fernandes, C. (2010)
The seismic performance of RC elements with plain reinforcing bars is particularly sensitive to the bond-slip mechanism. In this paper are described the cyclic tests performed on a two-spans beam with plain reinforcing bars and two beam-column joints with the same geometry and reinforcement detailing, one with plain reinforcing bars and the other with deformed bars. The main experimental results are presented and the comparison between the global behaviour of the two joints is established. A numerical model of the beam was developed within the OpenSees platform and calibrated with the experimental results. Particular attention was given to the bond-slip mechanism. Additional numerical analyses were developed without considering bond-slip. The comparison between the main numerical and experimental results shows the great importance of considering the bond-slip mechanism in the numerical models in order to have a precise simulation of the cyclic response of RC elements with plain reinforcing bars.